A review of the Generic Design Assessment (GDA) Public Dialogue Pilot (2015) for new nuclear build in the UK: lessons for engagement theory and practice. (6th June 2016) - Whitton, John; Parry, Ioan; Grundy, Colette; Lillycrop, Annabelle; Ross, David
Abstract: We have discussed previously that a community-based, asset-based approach is required to achieve any sense of how social sustainability can be defined in a community setting within the context of energy developments. Our approach aims to initiate a lasting change within 'energy' communities through building social capital; focusing on community assets not deficits to define their social priorities. Through deliberation, we develop an understanding of social sustainability so that a community is well placed to enter discussions with government and industry regarding large energy developments that will directly affect them. We review the 2015 Generic Design Assessment (GDA) Public Dialogue Pilot process for potential new nuclear reactors in the UK. We examine the aims of the dialogue, giving particular attention to a comparison between the national sampling of citizens for the GDA and the local community-based, deliberative approach we have proposed previously. We find an ongoing tension between 'national' engagement processes (such as the GDA Public Dialogue Pilot process) and the specific requirements of those energy communities that live adjacent or close to energy infrastructure, manifested here by a conflict between the requirements of the convenor and those of participants regarding priority issues for discussion. We also reveal a paradox; despite participant preference for a remote, internet-based engagement process, they agreed that face to face contact is a priority to encourage trust building between participants and the convenor of the process—a desired outcome of the process. The GDA Public Dialogue Pilot process has demonstrated that stakeholders are willing to engage with and be more directly involved in local energy-related decisions that affect them directly, provided there is opportunity to discuss locally-relevant and site-specific issues in addition to those of a broader nature. There exists a disparity and conflict between 'national' engagement processes and the 'local' priorities of those energy communities that are adjacent or close to energy infrastructure. In this process and others, we have seen an imbalance between the requirements of the convenor and those of participants regarding priority issues for discussion. This continues to be a persistent challenge for those convening stakeholder engagement events where the scope and context is not primarily site-specific. However, it is encouraging that convenors and participants alike continue to be willing to work towards resolving this.